CMPD2 - Braumann, Carlos (2008)
Secong international joint conference of the Conference on Mathematical Population Dynamics (MPD #8) and the Conference on Deterministic and Stochastic Models for Biological Interactions (DeStoBio #4). It took place in Campinas, Brazil, from July 16 to 20, 2007. Web site: http://www.cmpd2.ime.unicamp.br/